Provision of other medical work by Australian early-career general practitioners: a cross-sectional study - Parker Magin; Mieke van Driel; Neil Spike; Allison Turnock; Catherine Kirby; Jean Ball; Elizabeth Holliday; Andrew Davey; Amanda Tapley; Dominica Moad; Alison Fielding; Kristen FitzGerald; et al. (CSIRO Publishing, 2022)
Introduction There is a trend towards GPs diversifying their role by working in health areas beyond general practice. However, little is known about whether this trend is apparent among early-career GPs once they make the transition from training to independent practice. Aim To describe the prevalence of and characteristics associated with early-career GPs providing other medical work. Methods A cross-sectional questionnaire-based study of GPs ('alumni') who had fellowed within the past 2 years from three of Australia's nine regional training programs. The outcome factor was provision of medical work in addition to clinical general practice. Associations of independent variables (encompassing alumni demographics, current practice characteristics and vocational training experience) with the outcome were estimated using univariate and multivariable logistic regression. Results Of 339 responding alumni, 111 (33%) undertook other regular medical work. Sixty-five (59%) of these were in medical education. In multivariable analysis, factors associated with providing other medical work were having a spouse/partner not in the workforce (odds ratio (OR) 5.13), having done any training part-time (OR 2.67), providing two or more of home visits, nursing home visits and after-hours care (OR 2.20), working fewer sessions per week (OR 0.74), and currently working in an area of lower socio-economic status (OR 0.84). Having dependent children (OR 0.27), and being female (OR 0.43) were associated with not providing other medical work. Discussion In this study, many early-career GPs are providing other medical work, particularly medical education. Acknowledging this is important to general practice workforce planning and education policy.